Sosialisasi dan Pelatihan Manajemen Risiko pada UMKM Bisnis Food Court di Tangerang - Meike Elsye Beatrix; Hayu Kartika; Wieta Chairunesia (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
This community service program aims to improve MSME food court entrepreneurs' understanding of business risk management in Tangerang. The participants received training on basic risk management concepts, the identification of operational, financial, and food safety risks, and appropriate mitigation strategies through interactive workshops and case discussions. Evaluation was conducted using pre- and post-tests to measure knowledge improvement. The results indicate a significant increase in participants’ awareness of business risks and their ability to apply preventive actions in daily operations. This program is expected to strengthen business resilience, enhance service quality, and support the sustainability of community-based culinary enterprises.